2016
DOI: 10.1039/c5dt03384e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, DFT calculations, and electrochemical comparison of novel iron(ii) complexes with thione and selone ligands

Abstract: Thione- and selone-containing compounds and their metal complexes show promise as antioxidants, as antithyroid drugs, and for applications in lasers and blue light-emitting diodes. Although Cu(i/ii), Co(ii), Ag(i), and Zn(ii) coordination to thione and selone ligands has been broadly studied and Fe(ii) plays an important role in oxidative damage, very few iron-thione complexes and no iron-selone complexes are reported. Novel Fe(ii)-containing thione and selone complexes of the formulae FeL2Cl2, [FeL2(CH3CN)2](… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 96 publications
2
28
0
Order By: Relevance
“…The average value of the four non‐equivalent Fe–Se bond lengths of complex 1 is 2.48 Å (Table ), which is within the corresponding values observed for tetrahedral Fe II Se 4 ‐containing complexes identified in the CSD: [N(CH 3 CH 2 ) 4 ] 2 [Fe(SePh) 4 ] (2.46 Å), [Fe(1,10‐phen) 3 ][Fe(SePh) 4 ] (2.46 Å), [PPh 4 ] 2 [Fe(Se 4 ) 2 ] (2.45/2.43 Å), [N(CH 3 ) 4 ] 2 [Fe{SeC(CH 3 ) 3 } 4 ] (2.47 Å), [bis(1,3‐di‐ tert ‐butyl‐1 H ‐imidazol‐3‐ium)] 2 [Fe(SePh) 4 ] (2.45 Å), [Fe{(SeP i Pr 2 ) 2 N} 2 ] (2.47 Å) and [Fe(dmise) 4 ][BF 4 ] 2 , dmise = N , N′ ‐dimethylimidazoleselone (2.46 Å) . The recently reported structure of 1 SP surprisingly contains a square planar FeSe 4 coordination sphere .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The average value of the four non‐equivalent Fe–Se bond lengths of complex 1 is 2.48 Å (Table ), which is within the corresponding values observed for tetrahedral Fe II Se 4 ‐containing complexes identified in the CSD: [N(CH 3 CH 2 ) 4 ] 2 [Fe(SePh) 4 ] (2.46 Å), [Fe(1,10‐phen) 3 ][Fe(SePh) 4 ] (2.46 Å), [PPh 4 ] 2 [Fe(Se 4 ) 2 ] (2.45/2.43 Å), [N(CH 3 ) 4 ] 2 [Fe{SeC(CH 3 ) 3 } 4 ] (2.47 Å), [bis(1,3‐di‐ tert ‐butyl‐1 H ‐imidazol‐3‐ium)] 2 [Fe(SePh) 4 ] (2.45 Å), [Fe{(SeP i Pr 2 ) 2 N} 2 ] (2.47 Å) and [Fe(dmise) 4 ][BF 4 ] 2 , dmise = N , N′ ‐dimethylimidazoleselone (2.46 Å) . The recently reported structure of 1 SP surprisingly contains a square planar FeSe 4 coordination sphere .…”
Section: Resultssupporting
confidence: 77%
“…With respect to the coordination of [Ph 2 P(Se)NP(Se)Ph 2 ] – to Fe II , it should first be noted that the following literature complexes have been shown, by X‐ray crystallography, to unequivocally contain a tetrahedral FeSe 4 coordination sphere: [N(CH 3 CH 2 ) 4 ] 2 [Fe(SePh) 4 ], [Fe(1,10‐phen) 3 ][Fe(SePh) 4 ], [PPh 4 ] 2 [Fe(Se 4 ) 2 ], [N(CH 3 ) 4 ] 2 [Fe{SeC(CH 3 ) 3 } 4 ], [bis(1,3‐di‐ tert ‐butyl‐1 H ‐imidazol‐3‐ium)] 2 [Fe(SePh) 4 ], [Fe{(SeP i Pr 2 ) 2 N} 2 ] and [Fe(dmise) 4 ][BF 4 ] 2 , dmise = N , N′ ‐dimethylimidazoleselone . In addition, on the basis of spectroscopic and room temperature magnetometry studies, the [Fe{(SePPh 2 ) 2 CH} 2 ] complex, bearing a ligand which is similar to L, has been proposed to also contain a tetrahedral FeSe 4 core .…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of the free ligand (Figure A) showed a chemically irreversible behaviour ( E p = 0.734 V vs. SCE), which contrast with the chemically reversible and electrochemically quasi‐reversible behaviour obtained for similar compounds in DMSO and CH 3 CN. [15a], [15c], [15d], [16c] Nonetheless, the ligand oxidation in acetonitrile, is in good agreement with the oxidation of the S‐atom of the methimazole moiety present in the ligand structure . The oxidation wave for the 2 m m ligand solution has a current peak of 50.4 µA at 0.1 V s –1 similar to the one observed for ferrocene under the same conditions of 58 µA.…”
Section: Resultssupporting
confidence: 67%
“…The study of the redox properties as well as the mechanism involved in the voltammetric behaviour of this kind of coordination compounds is a current research topic due to the fact that the oxidation or reduction potentials are key parameters for their application as antioxidants, for the understanding of the catalytic activity of metalloenzymes and the formation of adsorbed metallic films . Moreover, electrochemical studies, on 1,3‐(disubstituted)imidazolyl‐2‐thione metal complexes, revealed a non‐innocent ligand (NIL) behaviour, that is the ligand tends to oxidise instead of the metal centre, thus stabilising the metal centre in low oxidation state; for instance protection of iron(II) has been observed in complexes containing monodentate 1,3‐dimethyl‐imidazolyl‐2‐thione (dmit) and 1,1'‐ethylenebis(3‐methyl‐4‐imidazolyl‐2‐thione) (ebit)[16a] ligands, Figure a. Another example is the spontaneous reduction of Cu II to Cu I complexes based on N , N' ‐dimethylimidazolyl‐2‐thione[15c] with the concomitant oxidation of the thione group to the corresponding disulfide compound, Figure b.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the popularity of NHCs, there are various reliable synthetic routes to these precursors, including many known substitution patterns. 4 In more recent years, the coordination chemistry of selenoureas has been explored more extensively, with transition metal complexes being investigated as potential catalysts for organic transformations, 5 models of biological systems, 6,7 or as solid-state materials precursors. 8,9 As selenium is a soft Lewis base, the mid to late transition metals have been a particular focus.…”
Section: Introductionmentioning
confidence: 99%